2015
DOI: 10.3920/bm2013.0097
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in microbiota species and fermentation products in a dietary model enriched in fat and sucrose

Abstract: The gastrointestinal tract harbours a "superorganism" called the gut microbiota, which is known to play a crucial role in the onset and development of diverse diseases. This internal ecosystem, far from being a static environment, could be willingly manipulated by diet and dietary components. Feeding animals with high-fat sucrose diets entails diet-induced obesity, a model which is usually used in research to mimic the obese phenotype of Western societies.The aim of the present study was to identify gut microb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
20
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 62 publications
7
20
0
1
Order By: Relevance
“…In the current investigation, the potential of quercetin to deeply modify general bacterial profile at family level is underlined, indicating an important reduction in the relative abundance of Erysipelotrichaceae family, in contrast to what it was found with trans-resveratrol administration alone or in combination. Likewise, it was previously demonstrated by our group [17] that Erysipelotrichi taxa was profoundly enlarged (1025.4 %) after a HFS diet treatment for 6 weeks [17]. Interestingly, concerning the enrichment found in the Bacteroidetes phylum, quercetin supplementation also deeply increased the abundance of Bacteroidaceae and Prevotellaceae families, which were stated to be negatively influenced in highfat-fed mice [45].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…In the current investigation, the potential of quercetin to deeply modify general bacterial profile at family level is underlined, indicating an important reduction in the relative abundance of Erysipelotrichaceae family, in contrast to what it was found with trans-resveratrol administration alone or in combination. Likewise, it was previously demonstrated by our group [17] that Erysipelotrichi taxa was profoundly enlarged (1025.4 %) after a HFS diet treatment for 6 weeks [17]. Interestingly, concerning the enrichment found in the Bacteroidetes phylum, quercetin supplementation also deeply increased the abundance of Bacteroidaceae and Prevotellaceae families, which were stated to be negatively influenced in highfat-fed mice [45].…”
Section: Discussionsupporting
confidence: 69%
“…high-fat diets [17,18], has been also demonstrated to be susceptible to modulation by a variety of components such as probiotics and prebiotics [19]. Apparently, non-digestible polysaccharides could come to the aid of proliferating "friendly bacteria" and enhance microbial diversity in the gut [20], which might contribute to the amelioration of obesity and obesity-associated metabolic disorders [21].…”
Section: Introductionmentioning
confidence: 99%
“…We found that TMAO was associated with added sugar intake (r = 0.23). Sucrose previously has been shown to modify the gut microbiome (46,47); thus, our findings possibly could indicate an indirect sugar effect on TMAO via changes to the gut microbiome.…”
Section: Tablementioning
confidence: 62%
“…Clostridium fusiformis was reduced significantly in feces of high-fat sucrose diet-induced obese rats (33). It is particularly interesting that Thomas et al (34) reported Clostridium fusiformis as widely predominant in barrier flora and as producing a barrier effect against Clostridium difficile infection, suggesting that Clostridium fusiformis is a beneficial bacterium for human health.…”
Section: Discussionmentioning
confidence: 95%